2013
DOI: 10.1177/0009922813515744
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Risk Factors in Childhood Urinary Tract Infection, Vesicoureteral Reflux, and Renal Scarring Management

Abstract: Approaches to the management of children with urinary tract infection (UTI), vesicoureteral reflux (VUR), and renal scars have been challenged and have become controversial over the past decade. It is difficult to determine when, how, and which patients will benefit from the diagnosis and management of this condition. Therefore, the issues of diagnostic imaging, observation, follow-up, and intervention tend to be decided more on a case-by-case basis, rather than by using an algorithm. Over the past few years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 120 publications
(313 reference statements)
0
18
0
7
Order By: Relevance
“…As remains uncertain whether identifying and treating children with VUR confers any true clinical benefit , thus existing guidelines do not recommend extensively investigating all children with a first febrile UTI, but limiting comprehensive testing to a subgroup of children considered at high risk for significant abnormalities. Consequently, a number of risk factors possibly associated with the presence of VUR, recurrence of UTIs and renal scars have been highlighted .…”
Section: Introductionmentioning
confidence: 99%
“…As remains uncertain whether identifying and treating children with VUR confers any true clinical benefit , thus existing guidelines do not recommend extensively investigating all children with a first febrile UTI, but limiting comprehensive testing to a subgroup of children considered at high risk for significant abnormalities. Consequently, a number of risk factors possibly associated with the presence of VUR, recurrence of UTIs and renal scars have been highlighted .…”
Section: Introductionmentioning
confidence: 99%
“…We found, parallel to increased reflux grading, abnormal DMSA finding was increased significantly. Therefore, children with high grade of VUR (more than grade 3) will get benefit from antimicrobial prophylaxis, because previous report showed in the presence of high grade VUR (grades 3 and more), the risk of APN will be high (21), however using antimicrobial agents in VUR grades 1 or 2 is challenging (22)(23)(24). Regarding the study by Friedman et al, presence of UTI with non E. coli agents was associated with higher reflux grading; however in our study, this correlation was not found (25).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early recognition of renal scars is very important. 7 The gold standard imaging method to assess renal parenchymal defects (i.e., hypoplasia, dysplasia, scars) is considered to be 99mTc-dimercaptosuccinic acid (DMSA) scintigraphy. 8 A cross-sectional study that combined patients with UTIs and/or vesicoureteral reflux (VUR) showed that focal DMSA defects were present in 15.5% of 565 children.…”
Section: Introductionmentioning
confidence: 99%
“…9 DMSA renal imaging can provide information regarding the degree of existing renal cortical abnormalities that may affect the management plan. 7 In addition, DMSA imaging can serve as a baseline for future comparison. 7 Even if it is well-tolerated, there are some concerns about accessibility, radiation exposure, and lengthy protocols in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation